1918
DOI: 10.1017/s0022172400007221
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Meningococcus Carrier-Rate in relation to density of population in Sleeping Quarters

Abstract: 1. A high meningococcus carrier-rate in a military unit denotes that dangerous overcrowding exists in this unit.2. Severe overcrowding (i.e. when beds are less than 1 foot apart) is usually accompanied by a carrier-rate (serological) of at least 20 per cent.(Twenty per cent. is the danger line indicated in the War Office Memorandum on Cerebro-spinal Fever, March 1917.)3. A carrier-rate of this height will usually imply that the mobilization standard of 40 square feet has been infringed, and also that beds are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1931
1931
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…." (7), and that 22% of civilians examined in an outpatient infirmary "although they had no relation to cerebrospinal fever" harbored in their nasopharynx organisms indistinguishable from the meningococci (8), a result confirming previous studies which showed that "meningococci are to be found in a considerable percentage of persons in whom no relation to cases of cerebrospinal meningitis is discoverable".…”
supporting
confidence: 78%
See 1 more Smart Citation
“…." (7), and that 22% of civilians examined in an outpatient infirmary "although they had no relation to cerebrospinal fever" harbored in their nasopharynx organisms indistinguishable from the meningococci (8), a result confirming previous studies which showed that "meningococci are to be found in a considerable percentage of persons in whom no relation to cases of cerebrospinal meningitis is discoverable".…”
supporting
confidence: 78%
“…It is sometimes difficult in these studies to determine whether a high carrier rate was associated with actual overcrowding, or to what extent a high carrier rate was in itself interpreted as evidence of overcrowding. A sharp rise in the noncontact carrier rate "is a sure a storm signal of imminent danger of an outbreak as it is a sign of overcrowding or of dangerously deficient ventilation" (7). (The latter was sometimes invoked in instances of otherwise unsatisfactory evidence of ''overcrowdingg".…”
mentioning
confidence: 99%
“…Carriage was highest among military populations. 59,65,75 Among civilian populations, carriage ranged from 4 to 18.8% although two-thirds of participants were less than 12 years old in the study where the lowest average carriage rate of 4% was reported. 37,57 It was reported that the presence of respiratory infections facilitates carriage but no evidence of association between respiratory infections and carriage was found in two studies.…”
Section: Discussionmentioning
confidence: 69%
“…Crowding, cigarette smoke, and alcohol would seem the most prominent candidates. Elevated carriage and disease have been linked to shared living accomodations and possibly crowding in studies evaluating spread in households and dormitories (7,10,15,18,21). Crowding in a campus bar environment is of shorter duration but often at much higher density than that observed in households and dormitories.…”
Section: Discussionmentioning
confidence: 99%